Uracil/H Symport by FurE Refines Aspects of the Rocking-bundle Mechanism of APC-type Transporters. - Zantza, Iliana; Pyrris, Yiannis; Raniolo, Stefano; Papadaki, Georgia F; Lambrinidis, George; Limongelli, Vittorio; Diallinas, George; Mikros, Emmanuel (J Mol Biol, 2023)
Transporters mediate the uptake of solutes, metabolites and drugs across the cell membrane. The eukaryotic FurE nucleobase/H symporter of Aspergillus nidulans has been used as a model protein to address structure-function relationships in the APC transporter superfamily, members of which are characterized by the LeuT-fold and seem to operate by the so-called 'rocking-bundle' mechanism. In this study, we reveal the binding mode, translocation and release pathway of uracil/H by FurE using path collective variable, funnel metadynamics and rational mutational analysis. Our study reveals a stepwise, induced-fit, mechanism of ordered sequential transport of proton and uracil, which in turn suggests that FurE, functions as a multi-step gated pore, rather than employing 'rocking' of compact domains, as often proposed for APC transporters. Finally, our work supports that specific residues of the cytoplasmic N-tail are involved in substrate translocation, in line with their essentiality for FurE function.
Keywords: Biological Transport; Cell Membrane; Ion Transport; Membrane Transport Proteins; Protons; Uracil